2011
DOI: 10.4049/jimmunol.1100447
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cell Surface Fas Expression Is Necessary and Sufficient To Sensitize Lung Fibroblasts to Fas Ligation-Induced Apoptosis: Implications for Fibroblast Accumulation in Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is associated with the accumulation of collagen-secreting fibroblasts and myofibroblasts in the lung parenchyma. Many mechanisms contribute to their accumulation, including resistance to apoptosis. In previous work, we showed that exposure to the proinflammatory cytokines TNF-α and IFN-γ reverses the resistance of lung fibroblasts to apoptosis. In this study, we investigate the underlying mechanisms. Based on an interrogation of the transcriptomes of unstimulated and TNF-α– … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 61 publications
5
67
0
Order By: Relevance
“…The mechanisms accounting for the increased resistance to apoptosis in IPF fibroblasts have not been completely defined. Studies show that decreased cell surface expression of the Fas receptor is likely to contribute because increasing Fas receptor expression is sufficient to sensitize these cells to Fasinduced apoptosis (33,34,36). Consistently, we have shown that PGE 2 enhances Fas-mediated apoptosis in lung fibroblasts while increasing expression of the Fas receptor (10).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The mechanisms accounting for the increased resistance to apoptosis in IPF fibroblasts have not been completely defined. Studies show that decreased cell surface expression of the Fas receptor is likely to contribute because increasing Fas receptor expression is sufficient to sensitize these cells to Fasinduced apoptosis (33,34,36). Consistently, we have shown that PGE 2 enhances Fas-mediated apoptosis in lung fibroblasts while increasing expression of the Fas receptor (10).…”
Section: Discussionsupporting
confidence: 71%
“…Fibroblasts have an inherent resistance to Fas-mediated apoptosis in vitro, although the response to Fas activation can be enhanced by (1) treatment with the protein translation inhibitor cycloheximide, (2) treatment with the antifibrotic mediator PGE 2 , or (3) treatment with proinflammatory cytokines (10,11,(33)(34)(35)(36). We assessed apoptosis in normal lung fibroblast cell lines (IMR-90 and CCL-210) and patient-derived primary fibroblasts from normal and IPF tissue after exposure to a Fas-activating antibody (Fas-Ab) with and without cycloheximide.…”
Section: Ipf Lung Fibroblasts Have Decreased Susceptibility To Fas-mementioning
confidence: 99%
“…The MRC5 cell line has been used for studying TGF-β signaling and fibrosis (47)(48)(49)(50)(51). The A549 cell line is frequently used in research regarding alveolar type II epithelial cells (52)(53)(54)(55).…”
Section: Activation Of `7 Nachr Promotes Transcription Of Fibrotic Gementioning
confidence: 99%
“…Myofibroblasts derived from patients with idiopathic lung fibrosis were shown to express Fas ligand and were capable of inducing apoptosis of epithelial cells. However, these myofibroblasts themselves appeared to be immuno-privileged and were resistant to Fas-induced killing (28,47,85). These findings, coupled to known alterations in GSH homeostasis in the fibrotic lung suggest that altered redox-based regulation of the apoptotic cascade may fuel the pathogenesis of lung fibrosis (Fig.…”
Section: S-glutathionylation Death Receptors and Lung Fibrosismentioning
confidence: 66%